2022
DOI: 10.1021/acscatal.2c01750
|View full text |Cite
|
Sign up to set email alerts
|

Cu Vacancy Induced Product Switching from Formate to CO for CO2 Reduction on Copper Sulfide

Abstract: Cu is commonly modified with sulfur to obtain high selectivity for formate since S can promote the formation of the key *OCHO intermediate along the formate pathway. In the present work, we demonstrate that Cu-vacancies on copper sulfide can surprisingly switch the formate pathway to the CO pathway, and the concentration of Cu vacancies can deterministically regulate the CO faradaic efficiency and partial current density. The J CO of SNC@Cu1.96S (Cu1.96S coated sulfur, nitrogen-co-doped carbon) can reach 37.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…Another idea suggests that the Cu vacancy in CuS catalyst plays an important role in CO 2 RR. , Cu vacancy would alter the electronic structures of the S sites in CuS catalyst and thus impeding the HCOOH generation pathway by increasing the free energy for *H formation. In addition, the reduced ratio of the Cu cations to surface S anions had weakened the adsorbate-metal interaction, which was favorable for CO generation via promoting the *COOH pathway . In this work, we conclude that the presence of V s in the CuS catalyst promotes CO production in CO 2 RR by lowering the energy barrier of the *COOH intermediates.…”
Section: Results and Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Another idea suggests that the Cu vacancy in CuS catalyst plays an important role in CO 2 RR. , Cu vacancy would alter the electronic structures of the S sites in CuS catalyst and thus impeding the HCOOH generation pathway by increasing the free energy for *H formation. In addition, the reduced ratio of the Cu cations to surface S anions had weakened the adsorbate-metal interaction, which was favorable for CO generation via promoting the *COOH pathway . In this work, we conclude that the presence of V s in the CuS catalyst promotes CO production in CO 2 RR by lowering the energy barrier of the *COOH intermediates.…”
Section: Results and Discussionmentioning
confidence: 66%
“…For instance, in the work by Zhao et al, CuS nanosheets grown on nickel foam (NF) were fabricated, and the nanosheet morphology had facilitated *CO protonation, which had enabled highly selective CO 2 RR to CH 4 over the CuS@NF catalyst . Li et al reported that Cu-vacancies formed in CuS catalysts altered the electronic structures of the S sites, increased the energy barrier of H* formation, and favored the formation of the *COOH intermediate, thus switching the formate pathway to the CO pathway …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen vacancy in catalysts has shown beneficial roles in promoting the activation of CO 2 for one thing and in accelerating electron transfer for another. However, how to maximize the advantages of vacancies still requires more delicate material designs [15,[25][26][27][28][29]. Due to the good conductivity, carbon paper and carbon cloth are commonly used to support powder electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…First, CO 2 is a thermodynamically stable and chemically inert molecule ( ), , meaning that we have to consume a substantial amount of energy for driving CO 2 RR at a practicable rate. Second, since there are many kinds of CO 2 reduction products and the equilibrium potentials of these electrochemical reactions are very close, it is difficult to obtain a single product. Finally, the competing hydrogen evolution reaction (HER) has a strong impact on the faradaic efficiency of CO 2 RR in aqueous solution. , To improve the activity and selectivity of CO 2 RR, researchers have introduced many useful strategies on catalyst design such as nanostructures, , crystal facets control, and defect engineering …”
mentioning
confidence: 99%